To Infinity and Beyond: Reducing Textbook Costs Through Librarian/Faculty Collaborations. Issue 3 (2nd October 2018) - Avila, Sandra; Wray, Christina C.
Abstract: As subject and distance learning librarians, we have a special interest in supporting our faculty and their needs as they explore alternative and more affordable textbook options for their students. In an increasingly digital environment, there are a wealth of resources available at little or no cost to students. Unfortunately, finding these resources can be challenging and time consuming for faculty. This is where librarians step in. Through careful planning and collaboration with faculty, we can help transition course reading to online and open resources. Librarians can assist in this process by helping faculty identify appropriate resources, helping integrate resources into online learning environments, and providing support for student access to materials. This paper will describe this process from start to finish, utilizing our experience supporting a faculty member with an Ethnobotany course textbook as it was transitioned to an online textbook option.